2017
DOI: 10.1016/j.joms.2017.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Following Surgically Assisted Rapid Palatal Expansion, Do Tooth-Borne or Bone-Borne Appliances Provide More Skeletal Expansion and Dental Expansion?

Abstract: According to the literature, to achieve more effective skeletal expansion and minimize dental expansion after SARPE, a BB appliance should be favored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…4,30 In contrast, a significant difference in skeletal expansion has been detected in favor of BB appliances rather than TB appliances in a previous study. 34 A subgroup analysis of premolar and molar expansion in that study showed that BB appliances were more effective in achieving skeletal expansion than TB appliances at the premolar and molar levels. However, at the dental level, no significant difference was seen between BB and TB appliances in the amount of expansion at the premolar and molar levels in our study.…”
Section: Discussionmentioning
confidence: 91%
“…4,30 In contrast, a significant difference in skeletal expansion has been detected in favor of BB appliances rather than TB appliances in a previous study. 34 A subgroup analysis of premolar and molar expansion in that study showed that BB appliances were more effective in achieving skeletal expansion than TB appliances at the premolar and molar levels. However, at the dental level, no significant difference was seen between BB and TB appliances in the amount of expansion at the premolar and molar levels in our study.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have evaluated the stability, technique, expansion protocols and complications of these appliances, 2,21,49-51,57-59 and a recently published systematic review and meta-analysis has investigated which appliance provides more skeletal and dental expansion. 66 However, there is still no consensus on which appliance has the best outcomes in terms of less dental and skeletal relapse and fewer complications in the postoperative period. 59 A comprehensive search strategy 67 was used in this systematic review, prioritising sensitivity over specificity by using the highest level of evidence available.…”
Section: Discussionmentioning
confidence: 99%
“…Nos modelos de gesso também houve aumento significativo das distâncias entre cúspides caninas, cúspides mesovestibulares dos primeiros pré-molares e cúspides mesovestibulares dos primeiros molares, demonstrando que houve uma expansão linea r da a rcada e não apenas inclinações dentárias. É importante salientar que, mesmo no procedimento de expansão maxilar assistida cirurgicamente, podem ocorrer movimentações dos dentes posteriores, visto que simultaneamente à abertura gradual da sutura palatina mediana a força liberada pelo aparelho expansor provoca a compressão do ligamento periodontal, com inclinação lateral dos processos alveolares, podendo causar vestibularização dos dentes posteriores [9].…”
Section: Discussionunclassified